Three Dimension Movie for the Students Ability in Narrative Writing - Fita Faridah (Universitas Islam Lamongan, 2016)
This present study is conducted in order to improve the students’ writing narrative text by using Three Dimension Movie. It has several steps the first is Pre-writing In this phase the teacher combined with writing process included: planning and drafting. The second is Whilst- writing activities, in this phase the teacher combined with writing process include: revising and editing and the third is Post-writing activities, post-writing tasks allow for reflection, sharing, or publishing of the final product. This study employed Classroom Action Research (CAR) as the research design. The procedure of the research involved four stages: planning the action, implementing, observing, and reflecting. Using three dimension movie is intended the students deep understood the story of movie.Keywords: writing narrative text, three demension movie, and classroom action research